How well prepared are pre-service teachers to teach early reading? A systematic review of the literature. Issue 2 (2nd July 2016) - Meeks, Linda; Stephenson, Jennifer; Kemp, Coral; Madelaine, Alison
Abstract: This review examined studies that had addressed opinions of pre-service teachers (PSTs) concerning their preparedness for teaching early reading skills to all students, the extent of their content knowledge, and their attitudes towards code-based and/or meaning-based approaches to early reading. From the limited amount of research available, it would appear that although most PSTs were confident in their ability to teach early reading skills, they had reservations regarding their ability to teach children who struggle to learn to read. In addition, even though the majority of primary and early childhood PSTs favoured a code-based approach to teaching early reading, many lack both the necessary knowledge, and the confidence, to implement such an approach. A more comprehensive investigation across teacher training institutions is needed to confirm these findings.